Pengaruh Halal Label, Eco Label, Environmental Knowledge, Religiosity Terhadap Purchase Intention Melalui Halal Green Awareness dan Attitude - Muhammad Fadhel Gunawan; Ratih Hendayani (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
In the modern era, consumers are increasingly concerned about the ethical and environmental aspects of the products they buy, especially Muslim consumers who adhere to Islamic principles such as halal certification. Halal certification and eco-labels are important factors that influence consumer purchasing behaviour, especially in Indonesia. This study aims to assess the influence of halal label, eco label, environmental knowledge, and religiosity on the purchase intention of Starbucks food and beverage products through green halal awareness and attitude, especially in the context of boycott in Indonesia. This study uses a quantitative approach with a causal research type, collecting data through Likert scales from 385 Starbucks consumers in Indonesia using non-probability sampling methods and SEM-PLS analysis with SmartPLS 4.0. The results showed a direct relationship between halal labelling, environmental knowledge, and religiosity with green halal awareness, as well as between religiosity and attitude, and between green halal awareness and attitude with purchase intention. However, there is no direct influence of eco-label and environmental knowledge on green halal awareness.